Dermatoskopie in Sonderlokalisationen: Nägel, akrale Haut, Gesicht und Mukosa = Dermoscopy in special locations : nails, acral skin, face, and mucosa - Hänßle, Holger; Müller-Christmann, Christine (Der Hautarzt, 2019)
The use of dermoscopy by dermatologists across Europe has become a standard examination for benign and malignant skin lesions and increasingly also for inflammatory skin diseases. However, based on the experience of the authors from numerous dermoscopy courses, knowledge about important dermoscopic features in special locations such as mucosa or nails is often limited. This may be explained by (1) a different anatomy of the skin and its adnexa in special locations in comparison to the remaining integument, (2) difficult technical access to special locations with a dermatoscope, and (3) a rather low incidence of malignant skin neoplasms in areas of special locations (with the exception of facial skin/scalp). This article aims at explaining dermoscopic characteristics and features of important benign and malignant lesions of nails, acral skin, face, and mucosa.